Association Between Lifetime Classic Psychedelic Use and Hypertension in the Past Year. Issue 5 (8th March 2021) - Simonsson, Otto; Hendricks, Peter S.; Carhart-Harris, Robin; Kettner, Hannes; Osika, Walter
Abstract : Supplemental Digital Content is available in the text. Abstract : Using data from the National Survey on Drug Use and Health (2005–2014), weighted to be representative of the US adult population, the present study investigated the association between lifetime classic psychedelic use and hypertension in the past year among adults in the United States. The results showed that respondents who reported having used a classic psychedelic at least once in their lifetime had significantly lower odds of hypertension in the past year after adjusting for several potential confounders (adjusted odds ratio, 0.86 [0.81–0.91]; P <0.0001). Notably, when analyzing the associations between hypertension in the past year and lifetime use of the main classes of classic psychedelics, namely tryptamines (N, N-dimethyltryptamine, ayahuasca, and psilocybin), lysergic acid diethylamide (a lysergamide), and phenethylamines (mescaline, peyote, and San Pedro), only the association with lifetime tryptamine use was significant (adjusted odds ratio, 0.80 [0.73–0.89]; P =0.0001). Though these associations are novel, rigorous randomized controlled trials are warranted to investigate potential causal pathways of classic psychedelics on blood pressure.